A novel triple pressure HRSG integrated with MED/SOFC/GT for cogeneration of electricity and freshwater: Techno-economic-environmental assessment, and multi-objective optimization. (1st April 2021) - Vojdani, Mehrdad; Fakhari, Iman; Ahmadi, Pouria
Highlights: A novel waste heat recovery unit, namely, triple pressure HRSG, is presented. Comprehensive exergy analysis is performed to address inefficiencies. Effect of key parameters on the performance enhancement is analyzed. Exergy efficiency, LCOE, and EMI were improved by 19%, 8.5%, and 21%, respectively. Abstract: In the present study, a novel integrated energy system comprising a multi-effect desalination unit (MED) and a solid oxide fuel cell (SOFC) integrated with a gas turbine (GT) is presented for power and freshwater production. Thus, SOFC fuel cell's waste heat is exploited by a novel design of the steam generator unit to run a triple pressure steam cycle. Using MATLAB software, the performance of the proposed system is investigated from energy, exergy, economic, and environmental aspects. A parametric study is conducted to assess the influence of key parameters. Moreover, dual- and tri-objective optimizations are performed to determine the best-operating conditions considering exergy efficiency, levelized cost of energy, and normalized emission as objectives. The results indicate that the proposed integrated system can enhance the system power generation, the exergy efficiency, and the normalized emission by 6.5%, 8.42%, and 5.8%, compared to the solid oxide fuel cell integrated with a gas turbine standalone. The results also show that the proposed integration leads to daily freshwater production of 1141 m 3 at a constant value of levelized cost of energy. According to the exergy analysis, solid oxide fuel cells influence the system's overall enhancement considerably because of the highest exergy destruction value. By employing two-objective optimization, results showed that the exergy efficiency and levelized cost of energy can improve by 18.8% and 11% compared to the base case. Although normalized emission was not considered as an objective function, 16.5% improvement was observed . 3D Pareto front of three-objective optimization revealed a linear correlation between the exergy efficiency and normalized emission.